"Regionalism, Localism and the Borderlands" - Šesnić, Jelena (2007)
It could be argued that in much of contemporary US ethnic literature there exists a tension between a highly particular and local place and a sense of its interconnection with more overarching either national or even trans-national, trans-border spaces. This tension is presumably well illustrated in the texts attributed to what is usually designated as Mexican American / Chicano literature, in view of the fact that it most often retains as its privileged setting the south-western United States, even as it crosses over the border, both in its physical sense (a dividing line between the USA and Mexico) or in its symbolic evocation (the open wound, the imposed division of the bronze continent, Aztlán or “ Nuestra América” ). These multiple articulations of specific regional and local sites have been highlighted notably in some early articulations of “ border studies” (Anzaldúa, J D Saldívar) but they continue to resonate even as this paradigm has arguably engaged lately with the concepts of postcolonial and international studies (Singh and Schmidt ; Michaelsen and Johnson). Taking as my starting point Chicano cultural-nationalist manifesto “ El Plan Espiritual de Aztlán” , as well as texts by Rolando Hinojosa (Klail City), Oscar Zeta Acosta (The Autobiography of a Brown Buffalo), Dagoberto Gilb (The Last Known Residence of Mickey Acuñ a) and Denise Chávez (Face of an Angel, Loving Pedro Infante), my argument will try to show how they, through memorable evocations of regional and local ways and practices, in fact transform the purview of American and ethnic (literary) studies, even as they celebrate precisely the local(ized) features of their settings, protagonists and plots. Thus, they show how a transnational, borderlands perspective is inseparably tied to its particular regional manifestations, rather than detached from them. They thus require a complementary critical approach containing both national and inter-national perspectives in American studies.